The development and modernization of the banking services in the light of the trend towards the economy knowledge, "the case of Algeria" - Ayach, Zoubir; Boukhil, Nacim (Milev Journal of Research and Studies, 2017)
knowledge economy as a new economic model to help keep up with the progress in the global development, particularly in the banking industry, and this is evident through the adoption of the Algerian government several projects for the development and modernization of banking services, and it seeks to integrate technological developments in the activity of Algerian banks, in order to create a new quality banking services characterized by speed, security, and in line with the wishes of customers and the requirements of this economic orientation, through this research we are trying to shed light on Algeria's efforts to develop and modernize the banking services in the light of the trend towards a knowledge economy..